1988
DOI: 10.1111/j.1095-8649.1988.tb05433.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of two ecologically distinct forms of Arctic charr, Salvelinus alpinus (L.), in Loch Rannoch, Scotland

Abstract: Gill-netted samples of Arctic cham from Loch Rannoch, Scotland were bimodal when tested by univariate and multivariate morphometric analyses. The separation into two morphs corresponded very closely (95-98%) with fish classified subjectively in the field as benthic or pelagic, based largely on colour differences and ecological observations. The benthic charr had relatively longer heads, larger eyes and more powerful jaws than the pelagic charr. Unlike sympatric niorphotypes described from Scandinavia and Green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…Head shape has a high level of functional significance and is critical in the detection, capture and consumption of prey items. It has been shown to be correlated strongly with diet (Gardner et al, 1988;Adams and Huntingford, 2002 (Thompson et al, 2008), but this study used non-selected microsatellite markers and cannot be used as evidence of selection. Lastly, plastic effects following translocation of fish species have often been described (Loch, 1974;Shields and Underhill, 1993;Lema and Nevitt, 2006), and cannot be ruled out as a major mechanism causing the differences between the populations in this study.…”
Section: Discussionmentioning
confidence: 92%
“…Head shape has a high level of functional significance and is critical in the detection, capture and consumption of prey items. It has been shown to be correlated strongly with diet (Gardner et al, 1988;Adams and Huntingford, 2002 (Thompson et al, 2008), but this study used non-selected microsatellite markers and cannot be used as evidence of selection. Lastly, plastic effects following translocation of fish species have often been described (Loch, 1974;Shields and Underhill, 1993;Lema and Nevitt, 2006), and cannot be ruled out as a major mechanism causing the differences between the populations in this study.…”
Section: Discussionmentioning
confidence: 92%
“…It has been concluded that the occurrence of charr variants, both between and within localities, expresses the outcome of adaptive radiation (Jonsson & Jonsson 2001), a phenomenon usually regarded as a first phase of speciation process (Skú lason & Smith 1995;Skarstein et al 2005). So far, comparative morphological studies conducted on Arctic charr have usually concentrated on coexisting (sympatric) morphs (e.g., Gardner et al 1988;Gíslason et al 1999;Adams & Huntingford 2002). So far, comparative morphological studies conducted on Arctic charr have usually concentrated on coexisting (sympatric) morphs (e.g., Gardner et al 1988;Gíslason et al 1999;Adams & Huntingford 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Loch Rannoch, Scotland, there are two ecologically distinct morphs, one pelagic and one benthic. These two morphs show differences in head size, head shape, colour, parr marks and diet (Gardner et al ., 1988; Walker et al ., 1988). There are also genetic differences between the two morphs (Hartley et al ., 1992), which are believed to be reproductively isolated with different spawning sites and seasons (Gardner et al ., 1988).…”
Section: Discussionmentioning
confidence: 99%